Primogeniture, Equal Sharing, and the U.S. Distribution of Wealth - Menchik, Paul L. (Quarterly Journal of Economics, 1980)
Bequest patterns to children are important in intergenerational models of the distribution of income and wealth. Economies that feature primogeniture will have a greater degree of inequality than those featuring equal division. This paper presents evidence on estate division among children by sex, birth order, family size, estate size, and asset composition. The results presented here are preference-generated not tax-induced due to the tax characteristics within the sampling region. It is shown that equal sharing among children is the rule, a result that casts doubt upon the "altruist" model of inheritance as advanced by Becker and Tomes.